SIRT1 stabilizes extrachromosomal gene amplification and contributes to repeat-induced gene silencing - Taniguchi, Ryonosuke; Utani, Koichi; Thakur, Bhushan; Ishine, Kazuho; Aladjem, Mirit I.; Shimizu, Noriaki (The Journal of biological chemistry, 2021)
Sirtuin 1 (SIRT1) is a protein deacetylase that maintains genome stability by preventing the activation of latent replication origins. Amplified genes in cancer cells localize on either extrachromosomal double minutes (DMs) or the chromosomal homogeneously staining region. Previously, we found that a plasmid with a mammalian replication initiation region and a matrix attachment region spontaneously mimics gene amplification in cultured animal cells and efficiently generates DMs and/or an homogeneously staining region. Here, we addressed the possibility that SIRT1 might be involved in initiation region/matrix attachment region–mediated gene amplification using SIRT1-knockout human COLO 320DM cells. Consequently, we found that extrachromosomal amplification was infrequent in SIRT1-deficient cells, suggesting that DNA breakage caused by latent origin activation prevented the formation of stable extrachromosomal amplicons. Moreover, we serendipitously found that reporter gene expression from the amplified repeats, which is commonly silenced by repeat-induced gene silencing (RIGS) in SIRT1-proficient cells, was strikingly higher in SIRT1-deficient cells, especially in the culture treated with the histone deacetylase inhibitor butyrate. Compared with the SIRT1-proficient cells, the gene expression per copy was up to thousand-fold higher in the sorter-isolated highest 10% cells among the SIRT1-deficient cells. These observations suggest that SIRT1 depletion alleviates RIGS. Thus, SIRT1 may stabilize extrachromosomal amplicons and facilitate RIGS. This result could have implications in cancer malignancy and protein expression.